Influence of Structured Plyometric and Mobility Training Programs on Speed and Flexibility Adaptations in Collegiate Male Basketball Players - Arun Prasanna; Mathews P Raj; Gautam Deshpande (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Speed and flexibility are essential physical components that influence performance in basketball. Training methods such as plyometric training and mobility exercises are widely used to enhance these components. However, the comparative effectiveness of these training methods on collegiate basketball players requires further investigation. Methods: In this study, 45 male basketball players from JAIN University, aged 18 to 25, were randomly assigned to three groups of fifteen: the mobility exercise group (MEG), the control group (CG), and the plyometric training group (PTG). Over eight weeks, the experimental groups followed their respective training programs, while the control group received no special instruction. Flexibility was tested using the sit-and-reach method, and speed was measured with a 50-meter run. Data was analyzed using Scheffé’s post-hoc test and ANCOVA at a 0.05 significance level. Result: The experimental group outshined the control group, showing clear improvements in both speed and flexibility. While both training techniques greatly increased flexibility, the mobility exercise group showed more speed improvement than the plyometric group. At the 0.05 significance level, the F-ratios for both the post-test and the adjusted post-test scores were found to be statistically significant. Conclusion: Plyometric training and mobility exercises are effective in improving speed and flexibility among collegiate male basketball players. Mobility exercises showed a comparatively greater effect on speed, while both training methods significantly improved flexibility, making them valuable components in basketball training programs.